THE EFFICIENCY FORMATION MECHANISM OF THE FREIGHT TRANSPORT SYSTEM IN TERMS OF THE VARIABLE NATURE OF DEMANDS FOR TRANSPORTATION - Smyrnova, O. Yu. (Science and Transport Progress, 2009)
The mechanism of formation of efficiency of freight motor transport system in conditions of variable character of demand for freightage is developed on the basis of space-time approach development to efficiency formation for difficult systems. In the article the definitions of the notions of freight motor transport system adaptability, standard operation conditions are given.